Application of Audio Media, To Produce Rhythmic Movement Creativity, Class 6 Public Alementary School Bahungin - Muhammad Audy Noorazmi; Arie Rakhman; Rahmadi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of the study was to determine the application of audio media for rhythmic movement learning in grade 6 of Public Alementary School  Bahungin. This study used a descriptive quantitative approach method. Data collection techniques were carried out through observations of grade 6 students, physical education, sports, and health teachers. The results of the study with 2/4 beats showed that the medium category in terms of rhythm and movement harmony (66.7%), high category movement variation (38.1%), medium category sense of melody (38.1%), and medium category rhythm and body coordination skills (38.1%). The results of 4/4 beats showed that the majority of students were in the high category in terms of rhythm and movement harmony (38.1%), high category movement variation (47.6%), high category sense of melody (47.6%), and medium category rhythm and body coordination skills (47.6%). The conclusion of the research results is the overall results in the application of audio media to produce rhythmic movement creativity in class 6 of Public Alementary School  Bahungin, 2/4 beats are in the medium category and 4/4 beats are in the high category.